Pengaruh Kepemimpinan Transformatif, Pengendalian Internal, Kompetensi SDM, dan Pemanfaatan TI Terhadap Kualitas Laporan Keuangan - Riska Putri Setyaningrum; Sasmito Widi Nugroho; Sugiharto Sugiharto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to see how the influence of transformative leadership style, internal control system, HR competence, and utilization of information technology affects the quality of financial reports in several agencies in Magetan Regency. A total of 112 respondents participated in this study through filling out questionnaires. This study utilizes quantitative methods and statistical analysis (multiple linear regression) to process the data obtained. The results showed that transformative leadership style, internal control system, and HR competence improve the quality of financial statements, but the utilization of information technology does not necessarily improve the quality of financial statements. the four factors collectively influence in improving the quality of financial statements.